Assessing clinical and biomarker characteristics to optimize the benefits of sacubitril/valsartan in heart failure - Litwin, Sheldon E.; East, Cara A. (Frontiers in Cardiovascular Medicine, 2022)
Of the various medical therapies for heart failure (HF), sacubitril/valsartan is a first-in-class angiotensin receptor-neprilysin inhibitor that combines sacubitril, a pro-drug that is further metabolized to the neprilysin inhibitor sacubitrilat, and the angiotensin II type 1 receptor blocker valsartan. Inhibition of neprilysin and blockade of the angiotensin II type 1 receptor with sacubitril/valsartan increases vasoactive peptide levels, increasing vasodilation, natriuresis, and diuresis. Left ventricular ejection fraction (LVEF) is widely used to classify HF, to assist with clinical decision-making, for patient selection in HF clinical trials, and to optimize the benefits of sacubitril/valsartan in HF. However, as HF is a complex syndrome that occurs on a continuum of overlapping and changing phenotypes, patient classification based solely on LVEF becomes problematic. LVEF measurement can be imprecise, have low reproducibility, and often changes over time. LVEF may not accurately reflect inherent disease heterogeneity and complexity, and the addition of alternate criteria to LVEF may improve phenotyping of HF and help guide treatment choices. Sacubitril/valsartan may work, in part, by mechanisms that are not directly related to the LVEF. For example, this drug may exert antifibrotic and neurohumoral modulatory effects through inhibition or activation of several signaling pathways. In this review, we discuss markers of cardiac remodeling, fibrosis, systemic inflammation; activation of neurohormonal pathways, including the natriuretic system and the sympathetic nervous system; the presence of comorbidities; patient characteristics; hemodynamics; and HF signs and symptoms that may all be used to (1) better understand the mechanisms of action of sacubitril/valsartan and (2) help to identify subsets of patients who might benefit from treatment, regardless of LVEF. Abbreviations: ACEi, angiotensin-converting enzyme inhibitor; ANP, atrial natriuretic peptide; ARB, angiotensin II receptor blocker; BNP, brain natriuretic peptide; cGMP, cyclic guanosine monophosphate; HF, heart failure; HFimpEF, heart failure with improved ejection fraction; HFmrEF, heart failure with mildly reduced ejection fraction; HFpEF, heart failure with preserved ejection fraction; HFrEF, heart failure with reduced ejection fraction; LV, left ventricular; LVEF, left ventricular ejection fraction; NP, natriuretic peptide; NT-proBNP, N-terminal pro B-type natriuretic peptide.